An exploratory study of the Financial Sustainability of the Non-Profit Sector in Lesotho - Malebo, Moroesi (Department of Social Development, 2020)
The non-profit sector plays a significant role in development in Lesotho. The sustainability of the NPOs is important; however, there is limited research on Lesotho’s non-profit sector, in particular, on its financial sustainability. This study has explored the financial sustainability of the non-profit sector in Lesotho in particular, the factors that affect the sustainability of non-profit organisations. A qualitative methodology was adopted which used a semi-structured interview guide. The data was collected primarily through in-depth interviews with 20 Non-Profit organizations based in Maseru, Lesotho. The sample was selected from organizations, which were registered with the Lesotho Council of Non-governmental Organizations. Purposive sampling, which used a non-probability sampling method, was chosen to select the 20 NPOs that participated in this study. The data was analysed and presented thematically according to the main research objectives. The findings revealed that the financial sustainability of Non-Profit Organizations in Lesotho is severely challenged. NPOs depend on donor funding as a major source of funding. The NPOs founded locally had a greater struggle to get funding than the international NPOs which were guaranteed the support of their international organizations. The sustainability of these NPOs was threatened by several factors, however, Lesotho’s political instability was a threat to all Non-profit organizations’ sustainability because it resulted in the withdrawal of external donor funding. The findings revealed that donor funding has dwindled over the past couple of years. Nevertheless, international donors were still the most consistent sources of funding for the NPOs in Lesotho. All the NPOs in this study received international donor funding. Only a few that received government grants, which was also very unsatisfactory. The data also revealed that the NPOs struggled to raise sufficient funds and the majority did not have staff who were devoted to fundraising. Key recommendations are that: the NPOs in Lesotho need to explore other income generating activities to improve their financial sustainability; they also need to strengthen their fundraising capacity by training their staff in fundraising; and, lastly, they need to improve their online presence, as the internet has become an important fundraising tool.